Budaya Mandar Pappasang Hubungannya Dengan Pembinaan Moral Masyarakat - Muhammad Syaeba (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
This study aims to assess the scientific work it in and Mandar culture pappasang relationship with moral development of society , qualitative descriptive study design. That becomes assessment data is the phrase / sentence that contains / contain moral messages Mandar. Sources of data for the assessment is a written record of books related to Mandar pappasang moral and oral data sources obtained from informants . The data collection ( 1 ) Seeking Informants and knowledge to provide inputs for the author , (2 ) carefully and thoroughly read books and research results that are relevant to the study. ( 3 ) Conducting interviews with informants who have extensive knowledge of the cultural background of Mandar , especially pappasang Manda. The results showed that the moral is contained in pappasang ethics or rules and advice ancestral grow and thrive in the midst of Mandar people, that need to be adhered to and heeded anytime and anywhere. This means that the noble values contained pappasang , not only applies to the past but also still relevant to be applied to people's lives mandar now.